A Rice WRKY Gene Encodes a Transcriptional Repressor of the Gibberellin Signaling Pathway in Aleurone Cells - Zhong-Lin Zhang; Zhen Xie; Xiaolu Zou; Casaretto, Jose; Ho, Tuan-hua David; Qingxi J. Shen (Plant physiology (Bethesda), 2004)
The molecular mechanism by which GA regulates plant growth and development has been a subject of active research. Analyses of the rice (Oryza sativa) genomic sequences identified 77 WRKY genes, among which OsWRKY71 is highly expressed in aleurone cells. Transient expression of OsWRKY71 by particle bombardment specifically represses GA-induced Amy32b α-amylase promoter but not abscisic acid-induced HVA22 or HVA1 promoter activity in aleurone cells. Moreover, OsWRKY71 blocks the activation of the Amy32b promoter by the GA-inducible transcriptional activator OsGAMYB. Consistent with its role as a transcriptional repressor, OsWRKY71 is localized to nuclei of aleurone cells and binds specifically to functionally defined TGAC-containing W boxes of the Amy32b promoter in vitro. Mutation of the two W boxes prevents the binding of OsWRKY71 to the mutated promoter, and releases the suppression of the OsGAMYB-activated Amy32b expression by OsWRKY71, suggesting that OsWRKY71 blocks GA signaling by functionally interfering with OsGAMYB. Exogenous GA treatment decreases the steady-state mRNA level of OsWRKY71 and destabilizes the GFP:OsWRKY71 fusion protein. These findings suggest that OsWRKY71 encodes a transcriptional repressor of GA signaling in aleurone cells.